WHEAT RESPONSE TO ACC-DEAMINASEFLUORESCENT PSEUDOMONADS WITH VARYING PHOSPHATE SOLUBILIZING ACTIVITY ON A PHOSPHORUS DEFICIENT SOIL - J. Afzal; Zia-ul-hassan1; N. Depar; M. Arshad; S.S. Rao; I. Rajpar; A.N. Shah (Journal of Animal and Plant Sciences, 2014)
Rhizobacterial phosphate solubilization supports plant nutrition under phosphorus (P) deficiency stress. In this filed study we evaluated wheat response to ACC-deaminase-containing rhizobacterial strains, with or without phosphate-solubilizing activity, under varying levels of soil applied phosphatic fertilizer. The experiment was conducted on a P-deficient soilby using randomized complete block split plot design involving two factors. Factor Ainvolved three P doses (in main plots), i.e. 0(Control), 42.5 and 85 kg P2O5g ha-1. Factor B included three rhizobacterial treatments (in sub plots), i.e. No rhizobacterial seed inoculation (control) and wheat seed inoculation with ACC-deaminase Pseudomonas fluorescens with or without P-solubilizing activity. P nutrition of wheat plants at half and full recommended dose increased various plant growth and yield parameters of wheat in a range of 7.4 to128% and 9.6 to 144%, respectively, against control. ACC-deaminase Pseudomonas fluorescens without or with P-solubilizing activity increased various traits of wheat plants in a range of 1.4 to38% and 2.9 to86%, respectively, against control. The study concluded that Pseudomonas fluorescens with dual activities of ACC-demainase and phosphate solubilization play significant role in enhancing wheat growth and yield under both low- and high-P sustainable agriculture.
Keywords: Wheat; Triticumaestivum L.; Phosphorus; Pseudomonas fluorescens; ACC-deaminase; phosphate-solubilization